A identificação de alunos com altas habilidades/superdotação na perspectiva de professores que atuam na educação básica - Salgado, Maria Luiza Cunha (2024)
The general objective of this research is to investigate the process of identification and referral of students with a possible diagnosis of high abilities/ giftedness in the classroom through the perspective of Brazilian primary teachers in both public and private schools. The specific objectives of the research are: (1) to investigate the conceptions of class teachers regarding inclusive education; (2) to identify the conceptions and knowledge these teachers have regarding high abilities/ giftedness, seeking to comprehend how these perceptions influence the identification process; (3) to verify the existing instruments for observing and identifying these students in the classroom; (4) to investigate whether the teacher’s initial and continuous training has equipped them for this activity. In order to achieve these objectives, semi-structured interviews were held out with Brazilian primary school teachers who have already identified high abilities/ giftedness indicators in students in their classrooms. The data analysis reveals a gap in the initial and continuing training of teachers that hinders the process of identifying these students, revealing a need for investment in this training and in the development of public educational policies that ensure the appropriate identification and systematic assistance of children with high abilities/ giftedness